Melaleuca leucadendra Pharmacological Network for Identifying Potential Target of Alcohol Dependence - Setiawan, Risma Ayu; Jamil, Ahmad Shobrun; Rofida, Siti; Muchlisin, M Artabah (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 3 (2023): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR)DO - 10.18860/planar.v3i0.2477, 2023)
Melaleuca leucadendra (ML) contains a compound that is potentially a candidate for alcohol dependence. Alcohol dependence is defined by desire, tolerance, anxiety with alcohol, and continuing to drink even though the consequences are dangerous. The study aims to analyze the potential of the ML compound content for alcohol dependence therapy within silico-based pharmacological chain analysis. ML compound data is obtained from the Knapsack database, screening of absorption, distribution, metabolism, and excretion (ADME) of the compounds ML with SwissADME, prediction of the protein of the target compounder ML with the Swiss TargetpPrediction, Gene cards, venny, analysis of the pharmacological network with String-DB and its visualization with Cytoscape version 3.10.0. The pathways correlated with therapy are dopamine receptors, dopamine carriers, serotonin, gamma-aminobutyric acid receptors, and toll-like receptors for known therapeutic target proteins: OPRM1, DRD2, ALDH2, ADH1B, ADH1A, ADH1C, ADH4, SLC6A3, CNR1, POMC, ARRB2, and NCS1. Alcohol-dependent therapies include alpha-Campholenal, Benzaldehyde, trans-Pinocarveol, Borneol, linalool, alfa-Terpineol, (-)-alpha-Bisabolol oxide B, alphaterpine acetate, and Caryophylla-4(148),15-dien-5alphaol.